Important considerations in commercial aircraft damage tolerance. (5th August 2014) - Swift, T.
An analytical method is presented in this paper for the damage tolerance evaluation of adhesively bonded aircraft structures using advanced computer technology. The method, based on a displacement compatibility approach using complex variable analysis, considers elastic–plastic shear displacement characteristics of the adhesive. The effects of adhesive delamination are accounted for together with stiffener yielding. The method developed illustrates that three layers of stiffening elements and three layers of adhesive can easily be accounted for analytically. It is possible to simulate yielding in any element of the stiffener and adhesive systems independently of each other. Delamination in any or all of the adhesive layers can be simulated independently. Two complex stiffening geometries are included to illustrate the effects of adhesive yielding and delamination on the crack tip stress intensity factor in cracked panels. It an be seen from the results that adhesive yielding and delamination are important considerations.